The Power of Mentoring and Digitization as Processes of Strengthening the Human Resource Departments' Activity - Majid, Hamid Hazim (Journal of Economic Development, Environment and People, 2019)
Human resources (HR) represent the core of any organization. The way the human resources activities are understood, managed, standardised and mentored is vital for the survival, development and success of any organization in market competitions. In the digitization era HR and HR departments activities contribute to the safety and efficiency of the company, sharing part of assets, investment and profits. The professionals working in the HR department (HRD) are undergoing a profound transformation of mentality and technological change as main challenges of finding specialists and retaining employees. There present research studies the way the coming years will influence the company top management and staffs’ activities so that the profit and market share not to be diminished or lost